B cell depletion reduces T cell activation in pancreatic islets in a murine autoimmune diabetes model - Da Rosa, Larissa C. (Diabetologia, 2018)
AIMS/HYPOTHESIS: Type 1 diabetes is a T cell-mediated autoimmune disease characterised by the destruction of beta cells in the islets of Langerhans, resulting in deficient insulin production. B cell depletion therapy has proved successful in preventing diabetes and restoring euglycaemia in animal models of diabetes, as well as in preserving beta cell function in clinical trials in the short term. We aimed to report a full characterisation of B cell kinetics post B cell depletion, with a focus on pancreatic islets. METHODS: Transgenic NOD mice with a human CD20 transgene expressed on B cells were injected with an anti-CD20 depleting antibody. B cells were analysed using multivariable flow cytometry. RESULTS: There was a 10 week delay in the onset of diabetes when comparing control and experimental groups, although the final difference in the diabetes incidence, following prolonged observation, was not statistically significant (p = 0.07). The co-stimulatory molecules CD80 and CD86 were reduced on stimulation of B cells during B cell depletion and repopulation. IL-10-producing regulatory B cells were not induced in repopulated B cells in the periphery, post anti-CD20 depletion. However, the early depletion of B cells had a marked effect on T cells in the local islet infiltrate. We demonstrated a lack of T cell activation, specifically with reduced CD44 expression and effector function, including IFN-γ production from both CD4(+) and CD8(+) T cells. These CD8(+) T cells remained altered in the pancreatic islets long after B cell depletion and repopulation. CONCLUSIONS/INTERPRETATION: Our findings suggest that B cell depletion can have an impact on T cell regulation, inducing a durable effect that is present long after repopulation. We suggest that this local effect of reducing autoimmune T cell activity contributes to delay in the onset of autoimmune diabetes. ELECTRONIC SUPPLEMENTARY MATERIAL: The online version of this article (10.1007/s00125-018-4597-z) contains peer-reviewed but unedited supplementary material, which is available to authorised users.